Comparison of Two Homogeneous Methods with an Ultracentrifugation Method to Measure HDL-Cholesterol: Using Sera from Patients with Hypertriglyceridemia: Cross Reaction of VLDL with the Homogeneous Methods - Ono, Yoshikazu; Mashige, Fumiko; Hashimoto, Yoshiaki; Okubo, Shigeo; Nakahara, Kazuhiko (Japanese Journal of Clinical Chemistry, 2002)
We compared the results obtained using two homegenous assays, the Daiichi method and the Kyowa method, with those obtained using an ultracentrifugation method employing sera from patients with serum triglycerides levels of 2.59 to 14.97g/l. The values obtained with the Daiichi method correlated well with those obtained with the ultracentrifugation method. Although the values obtained with the Kyowa method also correlated with those obtained with the ultracentrifugation method in most sera, significant differences were observed in four sera samples. Agarose electrophoresis showed that one of the four sera, which showed a lower HDL-cholesterol value using the Kyowa method, contained slow a HDL, and the other three, which showed higher HDL-cholesterol values using the Kyowa method, contained increased VLDL. HDL-cholesterol values of the (LDL + HDL) fractions obtained after ultracentrifugation of the three sera were similar with the two homogeneous assays. The Kyowa method, but not the Daiichi method, significantly reacted with the VLDL fractions of the three sera separated by gel filtration chromatography. None of the homogeneous methods showed abnormal reaction time courses for the three sera. These results suggest that the Kyowa method indicates higher HDL-cholesterol values in sera containing high concentrations of VLDL due to partial cross reaction with VLDL, as compared with the Daiichi method and the ultracentrifugation method.